PERBANDINGAN HASIL BELAJAR PESERTA DIDIK MUKIM DAN NON MUKIM DI SD PLUS CAHAYA BUDAYA KREMBUNG - Nur Wahyu Ningsih; Nurul Aini; Mahfudzil Asror (Jurnal Muassis Pendidikan Dasar, 2023)
This study aims to compare the learning outcomes of mukim and non-mukim students at Sd Plus Cahaya Budaya Krembung. This type of research uses a comparative study method. The subjects of this study were 4th grade students totaling 14 mukim students and 14 non-mukim students. The data collection technique of this research is the test. The main instrument of this research is the test sheet. The data were analyzed using prerequisite analysis test including normality test and homogeneity test, independent sample T-test. Based on the results of the analysis test research shows that there is a significant difference between the learning outcomes of mukim students and non-mukim students. Judging from the average written test results of mukim students was 64.78, while the test results of non-mukim students were 51.14. The sig value obtained is 0.010 < 0.05, which means that Ho is rejected. It can be concluded from the results of the Independent Sample T-test that there is a significant difference in the increase in student outcomes of mukim students and non-mukim students from the results of the written test.